2019
DOI: 10.3389/fbioe.2019.00239
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antibacterial Activity and in vivo Cytotoxicity of Biogenic Silver Nanoparticles as Potent Therapeutics

Abstract: Biogenic nanoparticles are the smartest weapons to deal with the multidrug-resistant “superbugs” because of their broad-spectrum antibacterial propensity as well as excellent biocompatibility. The aqueous biogenic silver nanoparticles (Aq-bAgNPs) and ethanolic biogenic silver nanoparticles (Et-bAgNPs) were synthesized using aqueous and ethanolic extracts of Andrographis paniculata stem, respectively, as reducing agents. Electron microscopic images confirmed the synthesis of almost spherical shaped biogenic sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(126 citation statements)
references
References 71 publications
10
115
0
1
Order By: Relevance
“…The extracts showed antioxidant activity according to the following order: aqueous seed extract > ethanolic seed extract > ethanolic flesh extract > aqueous flesh extract >> hexane extracts. According to Aparadh et al [49] and Hossain et al [50], antioxidant activity of plant extracts depend on the presence of respective secondary metabolites, such as flavonoids, tannins and phenolics. Another study reported that vitamin C is the indicator of antioxidant activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…The extracts showed antioxidant activity according to the following order: aqueous seed extract > ethanolic seed extract > ethanolic flesh extract > aqueous flesh extract >> hexane extracts. According to Aparadh et al [49] and Hossain et al [50], antioxidant activity of plant extracts depend on the presence of respective secondary metabolites, such as flavonoids, tannins and phenolics. Another study reported that vitamin C is the indicator of antioxidant activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the higher cytotoxicity of smaller nanoparticles can be explained by different chemical-physical properties occurring when the particle is formed by a lower aggregation of atoms. As an example, we can consider the observed increased ROS production of small nanoparticles as compared to that generated by the greater ones (Hossain et al, 2019). Other mechanisms associated with these silver-containing nanosystems are the disruption of the bacterial membrane, uncoupling of the respiratory electron transport, morphological changes (cytoplasm membrane detachment), DNA replication impairment, and protein expression alteration (Durán et al, 2016;Tang and Zheng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AgNPs have shown good in vitro compatibility with human and murine erythrocytes (Hossain et al, 2019), but they do exhibit toxicity to peripheral blood mononuclear cells (PBMCs; Shin et al, 2007). Moreover, in vivo studies on zebra fish made by Bao and colleagues show that AgNPs induce pathological changes on growth indices, oxidative/antioxidative status, neural signaling, Na/K-ATPase function, and antioxidant system in the intestine, but not in the liver, with male zebrafish being more sensitive than female (Bao et al, 2020).…”
Section: Translation To the Clinical Setting: Are Nanoparticles Safe mentioning
confidence: 99%